Pengaruh Kecerdasan Logis-Matematis Terhadap Kemampuan Literasi Matematika Dalam Menyelesaikan Soal Konteks Makanan Malang - Heny Puspita Anggraini; Azza Nur Lailah; Marhayati Marhayati; Mutiara Arlisyah Putri Utami (Program Studi Tadris Matematika Fakultas Tarbiyah Institut Agama Islam Al-Qolam Malang, 2025)
This study aims to examine the effect of logical-mathematical intelligence on students' mathematical literacy in solving problems based on the context of Malang traditional foods. The novelty of this study lies in the use of an ethnomathematics-based local cultural context to assess mathematical literacy. A quantitative approach was employed using an explanatory survey with a cross-sectional survey design. The population consisted of all eleventh-grade students of MA Annuriyah, and a saturated sampling technique was applied, resulting in a sample of 30 students. Data were collected using two instruments: a logical-mathematical intelligence test consisting of seven multiple-choice items and a mathematical literacy test consisting of six essay items, both of which had been validated by experts. Data were analyzed using simple linear regression, preceded by prerequisite tests including normality, linearity, autocorrelation, and heteroscedasticity tests. The results indicated that logical-mathematical intelligence had a significant effect on mathematical literacy, contributing 26.5% to the variance in students' mathematical literacy. The regression equation Y = –43,498 + 0,605X further indicated that each one-point increase in logical-mathematical intelligence was associated with a 0.605-point increase in mathematical literacy. These findings suggest that logical-mathematical intelligence is one of the fundamental factors supporting students' mathematical literacy achievement in contextual learning situations.